Decadal oscillation of lakes and aquifers in the upper Great Lakes region of North America: Hydroclimatic implications. Issue 2 (21st January 2014) - Watras, C. J.; Read, J. S.; Holman, K. D.; Liu, Z.; Song, Y.‐Y.; Watras, A. J.; Morgan, S.; Stanley, E. H.
Abstract We report a unique hydrologic time series which indicates that water levels in lakes and aquifers across the upper Great Lakes region of North America have been dominated by a climatically driven, near‐decadal oscillation for at least 70 years. The historical oscillation ( 13 years) is remarkably consistent among small seepage lakes, groundwater tables, and the two largest Laurentian Great Lakes despite substantial differences in hydrology. Hydrologic analyses indicate that the oscillation has been governed primarily by changes in the net atmospheric flux of water (P − E) and stage‐dependent outflow. The oscillation is hypothetically connected to large‐scale atmospheric circulation patterns originating in the midlatitude North Pacific that support the flux of moisture into the region from the Gulf of Mexico. Recent data indicate an apparent change in the historical oscillation characterized by an 12 years downward trend beginning in 1998. Record low water levels region wide may mark the onset of a new hydroclimatic regime.